Report on the Tuvarai-Aru, Akkarayan-Aru, and Pali-Aru valleys : irrigation in the Northern Province, Mullaittivu and Vilankulam districts - Parker, Henry, Irrigation Officer, Sri Lanka (Sessional papers ;, 1887)
Report submitted to the Parliament of Sri Lanka.